EFEKTIFITAS QUANTUM LEARNING BERBANTUAN ALAT PERAGA DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA DI SD BINA INSANI DESA SIALOGO - Masdelima Azizah Sormin; Benny Sofyan Samosir; Ainun Mardiah Lubis; Nurmaini Ginting; Rawani Indah Tanjung; Adinda Pratini Lubis (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This research is motivated by the low understanding of mathematical concepts among students at SD Bina Insani, Sialogo Village, due to the perception that mathematics is difficult and abstract. The study aims to determine the effectiveness of the Quantum Learning model assisted by teaching aids in improving the understanding of comparison concepts among sixth-grade students. The research method uses a quantitative approach with a Pre-Experimental One Group Pretest-Posttest design. The research sample consisted of 10 students randomly selected from a population of 20 students. The instrument used was a written test in the form of story problems administered before and after the treatment. Data analysis employed descriptive statistics and a paired sample t-test. The results showed an increase in the average score from 52.30 in the pretest to 78.50 in the posttest. Hypothesis testing obtained a significance value of 0.000 < 0.05, thus H? is rejected. It is concluded that Quantum Learning assisted by teaching aids is effective in improving students' understanding of mathematical concepts. This model creates an enjoyable learning experience and makes abstract concepts more concrete through direct learning experiences.   Keywords: Quantum Learning, Teaching Aids, Concept Understanding, Mathematics, Elementary School, Comparison   Abstrak: Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep matematika siswa di SD Bina Insani Desa Sialogo akibat anggapan bahwa matematika sulit dan abstrak. Tujuan penelitian adalah untuk mengetahui efektivitas model pembelajaran Quantum Learning berbantuan alat peraga dalam meningkatkan pemahaman konsep perbandingan siswa kelas VI. Metode penelitian menggunakan pendekatan kuantitatif dengan desain Pre-Experimental One Group Pretest-Posttest. Sampel penelitian berjumlah 10 siswa yang diambil secara acak dari populasi 20 siswa. Instrumen yang digunakan berupa tes tertulis berbentuk soal cerita yang diberikan sebelum dan sesudah perlakuan. Analisis data menggunakan statistik deskriptif dan uji paired sample t-test. Hasil penelitian menunjukkan peningkatan nilai rata-rata dari 52,30 pada pretest menjadi 78,50 pada posttest. Uji hipotesis memperoleh nilai signifikansi 0,000 < 0,05 sehingga H? ditolak. Disimpulkan bahwa Quantum Learning berbantuan alat peraga efektif meningkatkan pemahaman konsep matematika siswa. Model ini menciptakan pembelajaran menyenangkan dan mengkonkretkan konsep abstrak melalui pengalaman belajar langsung.   Kata Kunci: Quantum Learning, Alat Peraga, Pemahaman Konsep, Matematika, Sekolah Dasar, Perbandingan.